Innovation orientation and performance of small and medium-sized enterprises (SMES) in Ghana: evidence from manufacturing sector - Kassimu Issau; Innocent Senyo Kwasi Acquah; Robert Ipiin Gnankob; Zulaiha Hamidu (Innovation & Management Review, 2022)
Purpose - The purpose of this paper is to assess the influence of innovation orientation dimensions on the performance of manufacturing small- and medium-sized enterprises (SMEs) in Ghana. Design/methodology/approach - Probability sampling technique, particularly, simple random method, was used for this study. Approximately, 81% response rate was achieved from a total sample size of 346. Furthermore, PLS-SEM technique was used to determine the relationships among the study variables. Findings - The result showed that market innovation significantly predicted SMEs' performance. Conversely, non-significant positive nexus was established between process innovation and SMEs' performance as well as product innovation and SMEs' performance. Practical implications - Based on the outcome, the stakeholders in the SME sector should aim at improving their market, products and process innovations. Originality/value - Despite the importance attached to the employment of innovation in the SME sector by scholars in the extant literature, studies involving dimensions of innovation orientation on SMEs' performance were not much seen in literature. This study enriched literature by determining the relationships between the innovation orientation dimensions and SMEs' performance.
Keywords: 650; Ghana; Innovation orientation; Manufacturing sector; Performance; PLS-SEM; SMEs